2010
DOI: 10.2202/1548-923x.1965
|View full text |Cite
|
Sign up to set email alerts
|

Theory-Based Research of High Fidelity Simulation Use in Nursing Education: A Review of the Literature

Abstract: In this article, we explore the extent to which theory-based research is informing our understanding of high-fidelity simulation use in nursing education. We reviewed the primary literature archived in the Cumulative Index of Nursing and Applied Health Literature (CINAHL) and Proquest Dissertation and Theses for empirical reports using the key terms high-fidelity simulation and nursing from the years 1989 to 2009. Of the articles that matched our inclusion criteria: 45% made no use of theory; 45% made minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…Rourke, Schmidt, and Garga (2010) noted that one advantage to HFS clinical is that students are exposed to high-risk scenarios that they are not routinely exposed to in the traditional clinical setting. Madhavan (2006) stated that "simulation has emerged as the third leg in the stool of science and education" (p. 64).…”
Section: Introductionmentioning
confidence: 99%
“…Rourke, Schmidt, and Garga (2010) noted that one advantage to HFS clinical is that students are exposed to high-risk scenarios that they are not routinely exposed to in the traditional clinical setting. Madhavan (2006) stated that "simulation has emerged as the third leg in the stool of science and education" (p. 64).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of studies where high‐fidelity patient simulators were used, merely 10% of investigators adequately applied theory; 45% used no theory (Rourke et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting these theories, the NLN/JSF is specific to simulation and links elements of simulation experiences to outcomes. A more comprehensive theory such as this can better guide educators in selecting appropriate simulation learning experiences (Kneebone 2006) and can assist researchers in developing relevant research questions, interpreting results, and synthesizing results across studies (Rourke et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rourke, Schmidt, and Garga (2010) reported that approximately 45% of articles indexed to "high fidelity simulation" made no use of theory, and only 10% were categorized as adequately theory based. A number of theories have been used to design simulation learning experiences, including experiential learning (Lasater, 2007).…”
mentioning
confidence: 99%